2022
DOI: 10.1002/jaba.942
|View full text |Cite
|
Sign up to set email alerts
|

Training medical students to teach safe infant sleep environments using pyramidal behavioral skills training

Abstract: Medical personnel play a critical role in caregiver safe infant sleep education. However, training outcomes in the safe infant sleep training literature have been mixed. Promising approaches that warrant further investigation are the use of behavioral skills training and pyramidal training. The current study consisted of two experiments. Experiment 1 extended Carrow et al. (2020) and Vladescu et al. (2020) by teaching medical students safe infant sleep practices using behavioral skills training. Discriminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For example, instructors could provide the didactic and modeling portion of BST via a training video to large groups of trainees and then arrange short, small-group role-plays for the practice and feedback portion. Pyramidal training, or train-the-trainer arrangements, also might increase the accessibility of the training and make it more practical to embed within existing medical school curriculum or large health organizations (e.g., Mery et al, 2022 ). Continuing education for practicing professionals likely will need to incorporate asynchronous training modalities (i.e., on-line instructional modules and videos) to permit more flexible scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, instructors could provide the didactic and modeling portion of BST via a training video to large groups of trainees and then arrange short, small-group role-plays for the practice and feedback portion. Pyramidal training, or train-the-trainer arrangements, also might increase the accessibility of the training and make it more practical to embed within existing medical school curriculum or large health organizations (e.g., Mery et al, 2022 ). Continuing education for practicing professionals likely will need to incorporate asynchronous training modalities (i.e., on-line instructional modules and videos) to permit more flexible scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep‐related infant deaths have remained stable for the past few decades (Centers for Disease Control and Prevention, 2022), prompting additional research on how to train caregivers in arranging safe sleep environments. A growing number of studies have shown the effectiveness of BST to train adults to engage in safe infant sleeping practices (Carrow et al, 2020; Mery et al, 2022; Mery et al, 2023; Vladescu et al, 2020), thereby demonstrating the efficacy of the training protocol developed by Carrow et al (2020) and Vladescu et al (2020). Interestingly, we found outcomes similar to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated behavioral skills training (BST; DiGennaro Reed et al, 2018) to teach college students (Carrow et al, 2020), expectant caregivers (Mery et al, 2023;Vladescu et al, 2020), and medical students (Mery et al, 2022) to arrange an analogue infant sleeping environment that corresponded with the recommendations of the American Academy of Pediatrics (Moon et al, 2022a(Moon et al, , 2022b. In all studies, participants responded with low to moderate levels of correct responding across scored safe-sleeping categories (i.e., surface, materials, position) during baseline measures, and they subsequently reached the mastery criterion following the implementation of BST.…”
mentioning
confidence: 99%
“…As the literature on food allergies in schools identifies the nurse as the critical resource (Carlisle et al, 2010), involving the nurse in a training on safety responses to allergens could be a potential way to reach more students. Similar to Mery et al (2022), training the nurse and school administrators using pyramidal training (i.e., training trainees how to teach others a skill) would allow for them to then train all students in the school building who have food allergies as a part of the school curriculum.…”
Section: Discussionmentioning
confidence: 99%